(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
The research proposes to extract data of male and female consumers' image perception and preferences in yarn-dyed fabrics for spring and summer shirts. The Semantic Differential (SD) evaluation on representative fabric samples by two groups of subjects was accomplished following the standardized sensory evaluation procedures. The differences in terms of image perception in yarn-dyed fabrics between male and female subjects was identified through Levene homogeneity variance test and independent samples T-test, and the evaluation factors of subjects' image perception was classified into 6 factors through factor analysis. The relationships between image word-pairs and subjects' preferences were validated with regression analysis. Experiment results show an evident difference in terms of image perceptions, preferences and the factors affecting preferences of the yarn-dyed fabrics between male and female subjects. The quantitative data could consequently provide guidance to help designing and producing differentiated yarn-dyed fabrics for designated sex consumers.